Connectivity as emancipation: Towards a Post-Anthropocentric Governance of the Amazon - Terrenas, J.; Pereira, J. C. (Workshop: Law and Governance in the Anthropocene, 2021)
The Anthropocene commands a radical reconsideration of international relations both as an academic discipline (IR) and field of practice. Against this backdrop, an emerging group of scholars has recently engaged in the development of what can be designated as ‘post-anthropocentric IR’. Building upon the method of immanent critique, we provide two contributions to this literature. First, we offer a post-anthropocentric adjustment to the concepts of power and insecurity in emancipatory security theory. We reconsider power as connectivity and insecurity as fragmentation. Second, we build upon that to provide an analysis, critique and reconsideration of the Amazon rainforest as an object of regional governance. We begin by unpacking how extant governance practices are fragmenting the Amazon and allowing for the systematic erasure of local cultures and the more-than-human relations upon which they rely. We then explore a post-anthropocentric alternative that is already immanent within the region: the Andes-Amazon-Atlantic Corridor. Placing ecological and sociocultural connectivity as the referent to be protected, the corridor confronts existing regional policies and offers an emancipatory pathway for Amazonian governance. In the concluding section, we take the Amazon as an entry point to illuminate a set of aspects that can advance the post-anthropocentric agenda of IR.